Amatoxin: A Review. (3rd September 2012) - Allen, Brandon; Desai, Bobby; Lisenbee, Nate
Abstract : This paper presents a comprehensive review of amatoxin poisoning. The paper discusses the biochemistry of amatoxin, as well as the clinical manifestations of amatoxin ingestion. In addition, the evaluation of the patient with amatoxin ingestion is discussed, along with the treatment—including newer therapy—and the ultimate prognosis of the syndrome.